PROPHETIC EDUCATION AS THE FOUNDATION OF CURRICULUM INNOVATION: A REVIEW OF THE LITERATURE AND ITS RELEVANCE FOR UM METRO - Cahyono, Heri (Universitas Muhammadiyah Metro, 2025)
Prophetic education represents an alternative paradigm that emphasizes the core values of humanization, liberation, and transcendence in the educational process. This study aimed to critically examine the concept of prophetic education and evaluated its relevance as a foundational framework for curriculum innovation at the University of Muhammadiyah Metro. Employing a literature review method and a qualitative analytical approach, the study analysed academic literature and relevant institutional documents. The findings indicated that prophetic education could enrich curriculum orientation by balancing scientific mastery with character development and social responsibility. Although challenges persist in operationalizing this concept within a formal curriculum, strategic opportunities remain, particularly in value-driven institutions such as UM Metro. This study recommends a curriculum transformation that is not only responsive to global developments but also firmly rooted in progressive Islamic values hallmarks of Islamic higher education. Prophetic education thus proves to be both relevant and promising as a foundation for transformative curriculum development in the era of disruption.Pendidikan profetik merupakan paradigma alternatif yang menekankan nilai-nilai humanisasi, liberasi, dan transendensi sebagai inti proses pendidikan. Kajian ini bertujuan untuk mengkaji secara kritis konsep pendidikan profetik dan merefleksikan relevansinya sebagai fondasi inovasi kurikulum di lingkungan Universitas Muhammadiyah Metro. Penelitian ini menggunakan metode studi pustaka dengan pendekatan kualitatif analitis terhadap literatur akademik dan dokumen kelembagaan yang relevan. Hasil kajian menunjukkan bahwa pendidikan profetik dapat memperkaya orientasi kurikulum dengan menyeimbangkan antara penguasaan ilmu pengetahuan dan pembentukan karakter serta tanggung jawab sosial. Meskipun terdapat tantangan dalam operasionalisasi konsep ini ke dalam kurikulum formal, peluang strategis tetap terbuka lebar, terutama di institusi berbasis nilai seperti UM Metro. Kajian ini merekomendasikan perlunya transformasi kurikulum yang tidak hanya adaptif terhadap perkembangan global, tetapi juga berakar pada nilai-nilai Islam berkemajuan sebagai ciri khas pendidikan tinggi Islam. Pendidikan profetik terbukti relevan dan potensial menjadi landasan bagi kurikulum transformatif di era disrupsi.